2018
DOI: 10.1111/cpr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR‐1258 regulates cell cycle and inhibits cell proliferation by directly targeting E2F8 in CRC

Abstract: MiR-1258 may function as a suppressive factor by negatively controlling E2F8, thus, highlighting the potential role of miR-1258 as a therapeutic target for human CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 26 publications
3
81
0
Order By: Relevance
“…E2F8 has been reported to overexpress in lung cancer, breast cancer, colorectal cancer, ovarian cancer, prostate cancer, esophageal squamous cell carcinoma and HCC [8,[29][30][31][32][33]. Consistently, our results also indicated that E2F8 was up-regulated in HCC tumors and correlated with advanced tumor stage and AFP elevation.…”
Section: Discussionsupporting
confidence: 87%
“…E2F8 has been reported to overexpress in lung cancer, breast cancer, colorectal cancer, ovarian cancer, prostate cancer, esophageal squamous cell carcinoma and HCC [8,[29][30][31][32][33]. Consistently, our results also indicated that E2F8 was up-regulated in HCC tumors and correlated with advanced tumor stage and AFP elevation.…”
Section: Discussionsupporting
confidence: 87%
“…Procedures were described previously (24). LV2-hsa-miR-1224-5p-mimic vector (miR-1224-5p-mimics), LV2-hsa-miR-1224-5p-inhibitor vector (miR-1224-5p-inhibitor), and LV2 empty lentivirus as a negative control (miR-NC) were constructed by lentiviral vectors (GenePharma, Shanghai, China).…”
Section: Cell Transfectionmentioning
confidence: 99%
“…Report assay was conducted as previously described (24). The wild-type 3 ′ -UTR sequence of SP1 predicted to interact with miR-1224-5p, referred to as WT-SP1 3 ′ -UTR, together with a matched mutated sequence within potential binding sites, referred to as MUT-SP1 3 ′ -UTR, were synthesized by GenScript (Nanjing, China).…”
Section: Luciferase Report Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Some miRNAs were reported to be associated with above biological processes in cancers. miR-661 and miR-22 were reported to regulate chromatin remodeling [35,36], miR-122, miR-15a, miR-26, miR-29, mir-30 and let-7 were related to the transcriptional misregulation in cancer [37], miR-188, miR-638 and miR-1258 were involved in the cell cycle regulation [38][39][40].…”
Section: Function Of the Four Mirnasmentioning
confidence: 99%